Study on the On/Off Ratio of the Cylindrical Surrounding Gate CNT Transistor Using Nonequlibrium Greens Function Approach - Munna, M.; Das, P.; Huq, M. F.; Ahmed, I. (Journal of Scientific Research, 2015)
The effects of the nanotube diameter, channel length, gate dielectric constant and gate dielectric thickness on the on-off current ratio performance of cylindrical surrounding gate carbon nanotube transistors are studied using a ?-orbital tight binding simulation model. The focus is both on Schottky-barrier and the doped source-drain contact devices. The on current significantly improves with high-? gate dielectric, whereas off current decreases. The device on-off current ratio improves, from 6.33 × 105 to 1.5 × 106 for doped contact and from 0.61 × 104 to 1.22 × 104 for SB device with thinner gate oxide. Minimum leakage current increases with larger diameter tube but on-current has no significant improvement. I-V characteristics are independent of channel length when it is larger than 15 nm. Significant increase in off-current occurs due to scaling the channel length down to 10 nm but on-off ratio still exceeds 103. In all cases, on-off ratio is higher and the effect of scaling is more prominent for doped contact devices than SB contact devices.